Mostly ghostly #4 little camp of horrors - Stines, R.L. (New York, Delacorte Press., 2005)
When his brother, Colin, takes the pendant in which the ghostly Nicky and Tara's parents may be trapped, Max must follow him to Camp Snake Lake and try to retrieve the pendant before evil ghosts find it.
Keywords: English, Fiction